Influence of different yeast races on quality parameters and antioxidant activity of wines produced from blackcurrant - Panasyuk A.; Makarov S. (Техника и технология пищевых производств, 2018)
Fermentation is the main technological stage of wine production. The objective of the article is to determine the dependence of qualitative parameters of wine material obtained from blackcurrant on the taken yeast race. The authors studied the influence of yeast on the blackcurrant mash fermentation dynamics, formation of secondary products, content of biologically active substances and antioxidant activity of the obtained wine material. The authors used Saccharomyces of two types: Saccharomyces vini – Chernosmorodinovaya 7, K-17, Moskva 30, Vishnevaya 33, K-72, and Saccharomyces cerevisiae – «Red Fruit», WET 136, LW 317-29, UWY SP1. Mass fraction of total phenolic compounds content expressed in terms of gallic acid was determined applying spectrophotometric method using Folin-Chokalteuʼs reactant. Mass fraction of ascorbic acid was calculated using high-performance liquid chromatography. The authors measured antioxidant activity applying improved ABTS method on Shimadzu UV-1600 spectrophotometer (Japan). They found out that yeast races Saccharomyces cerevisiae had higher fermentation activity than Russian pure yeast races Saccharomyces vini. Saccharomyces cerevisiae surpassed Saccharomyces vini in sugar utilization and ethanol yield. The article reveals that fermentation with Saccharomyces cerevisiae having high fermentation capacity results in the increase of methanol content by 33–57% and decrease in ascorbic acid concentration by 69–83% compared to the wine base samples obtained using Saccharomyces vini. The authors established that phenolic compound concentration in the wine material depends on the period of contact with yeast and on the applied yeast race. They determined that antioxidant activity of the product mainly depends on ascorbic acid concentration and made a conclusion that yeast race determines product biological value and antioxidant activity substantially. The authors recommend to use Chernosmorodinovaya 7 in high quality blackcurrant wine production.